2018
DOI: 10.1080/01496395.2018.1433688
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fouling, cleaning and faecal contamination on the separation of water from urine using thermally driven membrane separation

Abstract: In this study, membrane distillation is evaluated as a technology for non-sewered sanitation, using waste heat to enable separation of clean water from urine. Whilst membrane fouling was observed for urine, wetting was not evident and product water quality met the proposed discharge standard, despite concentration of the feed. Fouling was reversible using physical cleaning, which is similar to previous membrane studies operating without pressure as the driving force. High COD reduction was achieved following f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…These low MW bile salts are responsible for the significant reduction in surface tension (55mN m −1 versus 73mN m −1 for water) due to their amphiphilic and hydrophobic contributions [28] . Regardless of this reduction in fluid surface tension, Kamranvand et al [19] did not observe wetting during the membrane distillation of urine even with a membrane of coarse pore radius, indicating reasonable process resilience to this specific organic matrix; these observations support the rationale for adoption of MD for direct potable reuse in space missions [12] . However, faecal contamination of urine did reduce membrane permeability due to the formation of a particle cake which introduced two effects: (i) an initial reduction to heat and mass transfer, which lowered water flux; and (ii) the subsequent introduction of wetting, which diminished water quality.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…These low MW bile salts are responsible for the significant reduction in surface tension (55mN m −1 versus 73mN m −1 for water) due to their amphiphilic and hydrophobic contributions [28] . Regardless of this reduction in fluid surface tension, Kamranvand et al [19] did not observe wetting during the membrane distillation of urine even with a membrane of coarse pore radius, indicating reasonable process resilience to this specific organic matrix; these observations support the rationale for adoption of MD for direct potable reuse in space missions [12] . However, faecal contamination of urine did reduce membrane permeability due to the formation of a particle cake which introduced two effects: (i) an initial reduction to heat and mass transfer, which lowered water flux; and (ii) the subsequent introduction of wetting, which diminished water quality.…”
Section: Introductionmentioning
confidence: 84%
“…Increasing interest has also been shown for its application to wastewater treatment, where waste heat can be used to provide the driving force for separation since this delivers the opportunity to recover higher quality water for a reduced cost to treatment [11] . Whilst the high flow rates for conventional sewage treatment make the energy balance difficult to reconcile, this can be realised in the decentralised treatment of concentrated blackwater [19] , where the elimination of flushwater markedly reduces flow to treatment by two orders of magnitude [14] . The present lack of technological options for decentralised blackwater treatment remains a critical barrier in providing proper sanitation to 2.4 billion people globally [40] , which leads to approximately 700,000 child deaths per year [5] and economic losses of around $260 billion annually worldwide due to lost productivity and medical cost associated with poor sanitation [16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical chlorine-resistant bacteria, including Methylobacterium, Pseudomonas, Sphingomonas, and Acinetobacter, were identified as significantly distinctive genera in the foulants after the pretreatment by 15 mg-Cl 2 /L chlorine. Kamranvand et al (2018) investigated treatment performance and fouling in MD for water reclamation of urine in decentralized systems. The authors concluded that permeate quality was not affected, and fouling was reversible.…”
Section: Biofilmmentioning
confidence: 99%
“…Iteration occurs throughout the PD process and can have different causes and outcomes (Wynn, 2007). With its earliest forms dating back to the 1930s (Larman & Basili, 2003), the cyclical repetition of testing and (re-)designing can be welcomed as a driver of positive design change, or as a wasteful, costly delay in a PD project (Ballard, 2000;Le et al, 2010;Wynn & Eckert, 2017), but it is undeniable that iteration occurs in nearly every PD process, particularly for complex products (Wynn & Eckert, 2017).…”
Section: Iterationmentioning
confidence: 99%